Parâmetros genéticos para caracteres de crescimento, espessura de casca e densidade básica da madeira em progênies de Eucalyptus urophylla S.T. Blake - Pupin, Silvelise [UNESP]; Zaruma, Darlin Ulises Gonzalez [UNESP]; De Souza, Cidinei Santos [UNESP]; Cambuim, José [UNESP]; Coleto, Angélica Leonel [UNESP]; Alves, Patrícia Ferreira [UNESP]; Pavan, Bruno Ettore [UNESP]; De Moraes, Mario Luiz Teixeira [UNESP] (My University, 2017)
Volumetric production has been a priority in forest breeding programs. However, it is necessary to consider wood quality for the raw material supply that increases efficiency and yield. Thus, the aim of this study was to estimate genetic parameters, genitic correlations and selection gains for growth traits (diameter), bark thickness and basic density of wood in progênies of Eucalyptus urophylla. For this, we used wood discs removed at DHB and half the commercial height, from trees thinned in an open pollination progeny with 33 genotypes and two provenances (Rio Claro-SP and Três Lagoas-MS), located in Selvíria-MS. Estimates of genetic parameters were obtained using the REML/BLUP method. The best performance for growth was found in the Rio Claro provenance. Genetic differences in wood density between the provenances were not detected. The provenance of Três Lagoas showed a coefficient of genetic variation > 14% (diameter) and strong genetic control (heritability > 0.6 and accuracy > 78%). For wood quality, Rio Claro stood out in the estimates of heritability (> 0.6-DBM and ECD), achieving a higher accuracy of 79%. Contrasting results were found for the genetic correlation between the two sources. For obtaining genetic materials with higher density wood, the selection for DBM is advantageous.
Genetic parameters for growth traits, bark thickness and basic density of wood in progenies of Eucalyptus urophylla S.T. Blake
Keywords: REML/BLUP.; Tree breeding; Wood quality